A post-mortem study of commercial 18650 lithium-ion cells with LiNi0.5Co0.2Mn0.3O2//Graphite chemistry after prolonged cycling (> 7000 cycles) with low C-rates. (20th May 2021) - Weisenberger, Christian; Meir, Betina; Röhler, Sebastian; Harrison, David K.; Knoblauch, Volker
Highlights: Data for long-term cycling (> 7000 cycles) with low C-rates. State-of-the-art commercial cell chemistry (NCM532//Graphite). Detailed post-mortem analysis with complementary methods. Ageing mainly affected by the positive electrode whereas anode stays intact. Abstract: In this study the results of the post-mortem analysis of commercial 18650 lithium-ion cells with LiNi0.5 Co0.2 Mn0.3 O2 //Graphite chemistry after long-term cycling (>7000 cycles) with low C-rates (0.5C) are presented. To identify ageing mechanisms and to investigate their contribution to the overall ageing of the cell, extensive post-mortem analysis was carried out employing a broad spectrum of electrochemical and physicochemical methods including electrochemical impedance spectroscopy (EIS), electrochemical investigation of rebuilt half cells, X-ray computed tomography (CT), X-ray diffraction analysis (XRD) and scanning electron microscopy (SEM) combined with energy dispersive X-ray spectroscopy (EDS). Results show that the overall capacity loss of the cell is mainly caused by the capacity loss of the positive NCM523 cathode, whereas the graphite anode basically stays intact. The degradation of the cathode, i.e. its reduced ability to store and release lithium is caused by a combination of different effects such as mechanical degradation of the electrode, including micro-cracking of NCM particles provoking electrolyte consumption and crystallographic changes of the active material. Graphical abstract: Image, graphical abstract